Strand 4: Developing a Virtual College - Ward, Holly; Tracey, Karina; Barker, Mary (Proceedings of the International Conference on Networked Learning, 1998)
This paper discusses recent research into on-line educational services designed to support lifelong learning. These services support learners working in remote or isolated environments, as well as those in traditional learning environments. The case study used as an example was a collaborative project in the FE sector managed by BT Laboratories (BTL) and Northern Colleges Network (NCN). The aim was to evaluate an intranet based service, called CollegeComplete, which offered on-line resources over the network, as well as communication cools such as audio, data and text conferencing to enhance the learning experience and support social interaction.